2005
DOI: 10.1007/s11661-005-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal growth of TiB2 crystals during sintering of TiB2-Ni3(Al,Ti) cemented borides

Abstract: cermets present both normal and abnormal growth of faceted titanium diboride (TiB 2 ) grains during liquid-phase sintering. Abnormal grain growth (AGG) is preferentially found at high sintering temperatures in specimens processed from powder mixtures with a wide particle size distribution. The WC additions to the initial powder mixtures have proved efficient in reducing the number and size of these large TiB 2 grains. However, the sinterability of these materials is dramatically reduced, which suggests that Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In order to eliminate the effect of impurities those cermets were fabricated using high purity elemental powders. Similar attempts to modify the matrix phase were emphasized by Azkona et al [4] for Ni-containing TiB 2 -based composites, as well as reported recently by Zhang and coworkers [15] for Al-matrix cermets.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In order to eliminate the effect of impurities those cermets were fabricated using high purity elemental powders. Similar attempts to modify the matrix phase were emphasized by Azkona et al [4] for Ni-containing TiB 2 -based composites, as well as reported recently by Zhang and coworkers [15] for Al-matrix cermets.…”
Section: Introductionsupporting
confidence: 68%
“…MPa [4] can be reached for nearly monophasic TiB 2 material, while the same properties for unreinforced Fe are E= 210GPa and σ 0.2 = 135MPa, respectively [30]. The broken pieces after the compression test revealed cracks propagated in a plane oriented at 45° to the loading direction.…”
Section: Mechanical Propertiesmentioning
confidence: 86%
See 2 more Smart Citations
“…As the physical properties of materials can change drastically with the formation of abnormal grains, the control of AGG has been an essential subject for materials development in academia as well as in industry. Many theories and models have been developed to explain AGG in both ceramic and metallic systems .…”
Section: Introductionmentioning
confidence: 99%